-6.5(4y+6)-2.9(3y-5)=

Simple and best practice solution for -6.5(4y+6)-2.9(3y-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6.5(4y+6)-2.9(3y-5)= equation:


Simplifying
-6.5(4y + 6) + -2.9(3y + -5) = 0

Reorder the terms:
-6.5(6 + 4y) + -2.9(3y + -5) = 0
(6 * -6.5 + 4y * -6.5) + -2.9(3y + -5) = 0
(-39 + -26y) + -2.9(3y + -5) = 0

Reorder the terms:
-39 + -26y + -2.9(-5 + 3y) = 0
-39 + -26y + (-5 * -2.9 + 3y * -2.9) = 0
-39 + -26y + (14.5 + -8.7y) = 0

Reorder the terms:
-39 + 14.5 + -26y + -8.7y = 0

Combine like terms: -39 + 14.5 = -24.5
-24.5 + -26y + -8.7y = 0

Combine like terms: -26y + -8.7y = -34.7y
-24.5 + -34.7y = 0

Solving
-24.5 + -34.7y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '24.5' to each side of the equation.
-24.5 + 24.5 + -34.7y = 0 + 24.5

Combine like terms: -24.5 + 24.5 = 0.0
0.0 + -34.7y = 0 + 24.5
-34.7y = 0 + 24.5

Combine like terms: 0 + 24.5 = 24.5
-34.7y = 24.5

Divide each side by '-34.7'.
y = -0.7060518732

Simplifying
y = -0.7060518732

See similar equations:

| 395+77x=1319 | | -6x-20=-6 | | (4x+y)(3x-4y)= | | 5x-7=2x-34 | | -6x+20=-6 | | (6x-y)(3x-2y)= | | 290+74x=1474 | | -6(2p+4)-36=4(3p+3) | | -2(0)-6y=6 | | (x+2y)(2x+3y)= | | x^2=-6 | | 7-10n+5n=22-90 | | (-x-4)(4+3x)= | | 3-2=1 | | 4x^2=8x+5 | | 4(c-5)+9=6+c-17 | | 4y=8x-12 | | v^2x^2-9x^2+v^2n^2-9n^2=0 | | 5a-8.7=2.6a-2.22 | | 3(0)-4y=24 | | 2a+1.8=4.3a-14.99 | | 3x-4(0)=24 | | (2x+5)(4x-3)= | | 2b(7)=11 | | (4x-9)(3x+1)= | | 0=3x-9 | | 8m+16=0 | | (3x+2)(2x+5)= | | -4x-2(0)=8 | | graphy=-4a^2+2a+2 | | s=116t-1+16t | | A+(B+C)=(A+B)+C |

Equations solver categories